Cancel culture and nude living on virtual media: A case of Guru Mizan Qudsiyah Lombok - Muhammad Fikri; Ishak Hariyanto; Donie Kadewandana (Islamic Communication Journal, 2022)
Virtual media has a major influence on human life as a means of interaction and has even become a major force for society in controlling social change. Nonetheless, human interaction in virtual media is haunted by the pain of boycott and rejection. This study aims to examine the cancel culture phenomenon that occurs in virtual media. This study uses a qualitative method in which the primary data is taken from Youtube and articles related to the issue of cancel culture. Data on the cancel culture phenomenon experienced by Tuan Guru Mizan Qudsiyah from Lombok on YouTube media were analyzed using Pierre Bourdieu's genetic structuralism theory. The results of the study reveal that there is a cancel culture: boycotts or rejection because the statements and actions of Tuan Guru Mizan Qudsiyah on YouTube in 2020 are considered to have damaged public psychology. Tuan Guru Mizan's lecture on YouTube went viral because of his statement insulting the tombs of Lombok's saints who were considered sacred and was eventually canceled by a mob who then attacked and burned his pesantren. This study contributes to the formation of a new virtual space based on the value of Islamic communication, where cancellation occurs if friendly Islamic communication is not implemented.***Media virtual memiliki pengaruh besar bagi kehidupan manusia sebagai sarana berinteraksi bahkan menjadi kekuatan besar bagi masyarakat dalam mengendalikan perubahan sosial. Meskipun demikian, interaksi manusia di media virtual dihantui oleh pedihnya boikot dan penolakan. Studi ini bertujuan mengkaji fenomena ‘cancel culture’ yang terjadi dalam media virtual.  Studi ini menggunakan metode kualitatif dimana data primer diambil dari Youtube dan artikel terkait isu cancel culture. Data tentang fenomena cancel culture yang dialami oleh Tuan Guru Mizan Qudsiyah asal Lombok pada media YouTube dianalisis dengan menggunakan teori strukturalisme genetik Pierre Bourdieu. Hasil kajian mengungkapkan adanya budaya batal: boikot atau penolakan karena pernyataan dan tindakan Tuan Guru Mizan Qudsiyah di YouTube pada tahun 2020 yang dinilai mencederai psikologi publik. Ceramah Tuan Guru Mizan di YouTube menjadi viral karena pernyataannya yang menghina makam para wali Lombok yang dianggap keramat dan akhirnya dibatalkan oleh massa yang kemudian menyerang dan membakar pesantrennya. Kajian ini berkontribusi pada pembentukan ruang virtual baru berbasis nilai komunikasi Islam, dimana pembatalan terjadi jika komunikasi Islami yang ramah tidak diterapkan.